Cutaneous malignant melanoma with rarest combination of prostatic and splenic metastases on fluorodeoxyglucose (FDG) positron emission tomography—computed tomography scan - Shah, Digish; Odedara, Prakash (World Journal of Nuclear Medicine, 2020)
Cutaneous malignant melanoma (MM) metastases to prostate and spleen are very rarely experienced in clinical setting. As per our knowledge, coexistence of prostate and splenic metastatic MM is not reported worldwide. We are presenting a case of 70-year-old male patients with biopsy and clinically proven case of multifocal cutaneous malignant melanomatous lesions having multiple metastatic lymph nodes and systemic metastases, including prostate and spleen. This is the first case reported worldwide having a combination of prostate and splenic metastases.
Keywords: Fluorodeoxyglucose (FDG); malignant melanoma; positron emission tomography-computed tomography; prostatic-splenic metastasis